S2K-Leitlinie Hilfsmittelberatung bei Harninkontinenz der DGU – Prozess, Geltungsbereich, Erfassung der Harninkontinenz - Wiedemann, Andreas; Manseck, Andreas; Stein, Joachim; Kirschner-Hermanns, Ruth; Froehner, Michael; Butea-Bocu, Marius; Fiebig, Christian; Piotrowski, Alexander; Gleißner, Jochen; Linne, Clemens; Liebald, Timo; Schorn, Heribert; et al. (Aktuelle Urologie, 2025)
Background Counselling regarding a planned provision of medical aids is currently neither reimbursed nor regulated in Germany. It is offered by a range of providers with employees with varying levels of qualification and may be provided in a personal conversation, by phone, or remotely. In many cases, counselling is omitted entirely between the prescription and trial use or delivery of the product. The quality of medical aids counselling, which plays a key role in temporary, supportive or palliative care for urinary incontinence, is therefore considered problematic. Objective In 2019, the working group “Geriatric Urology” of the German Society for Urology published the first guideline on the counselling process related to the provision of medical aids. An updated version is currently available and has been listed by the Association of the Scientific Medical Societies. The underlying idea was to define quality standard in Germany for the individual components of the counselling process – from identifying the type of incontinence and its severity to product trial use, the counselling setting, the counselling itself, the qualification of the counselling personnel, and the communication between prescribing physicians, service providers, and patients. Material and Method This article presents the published guideline sections regarding the counselling process, its scope, and the assessment of urinary incontinence, including information relevant to patients. Discussion As medical aids counselling is expected to be financed from the low reimbursement rates provided by statutory health insurers for what is defined as an “appropriate and sufficient” supply – typically amounting to less than EUR 15 a month – more and more providers are withdrawing entirely from the sector of medical aids provision. Others continue to supply medical aids but offer no counselling at all or only to a very limited extent. The guideline “Medical Aids Counselling for Urinary Incontinence” developed by the working group “Geriatric Urology” of the German Society for Urology is meant to define quality standards, also with a view to a political discussion on reimbursement rates.
CRIS-Team Scopus Importer:2025-09-12